Scale and Scope Economies in the Tunisian Insurance Industry - Hamdani, Hanene (Journal of Posthumanism, 2025)
The purpose of this paper is to estimate scale and scope economies in the Tunisian insurance industry. At the best of our knowledge this is the first empirical study dealing with scale and scope economies in the Tunisian context. To investigate the economies of scale and of scope we use stochastic translog cost frontier. The model is estimated on a panel of 10 companies observed over the period 2014-2023. These companies form a representative sample of the Tunisian insurance industry as they have more than 95% of the market share on claims or premiums. Furthermore, we consider that all these companies share the same technology of production. The construction of such frontier requires an appropriate definition of outputs and input prices. We consider two factors of production: labor and capital to produce five outputs, i.e., automobile, group health, various risks, fire and life insurance. Our findings indicate that there exist significant economies of scale for insurance companies. But we do not observe systematic evidence of significant cost complementarities between insurance products, nor do we note significant economies of scope. No cost complementarities exist between the two main product lines of property/liability and automobile. Furthermore, there is some evidence of diseconomies of scope.